Efeito da estabilidade da transferência metálica (respingos) na soldagem MIG/MAG por curto-circuito sobre a geração de fumos e gases - Meneses, Valter Alves de (2013)
The best short-circuit welding condition in the GMAW process is not the one that will necessarily result in a lower variation of electrical signals, but rather that which provides greater transfer regularity and with transfer being dominated by surface tension. This behavior is related to transfer stability. It is known that the greater the transfer stability, the greater the penetration, the better finish to the bead and the lower amount of spatter. This study had as its main aim the analyzes and evaluation of the effect of the stability of short-circuit metal transfer of the GMAW welding process on the emission levels of metal fumes and gases and on the morphology and composition of the fumes generated. Using various mixtures of an Argon and CO2 and O2 base as protective gases and maintaining the average current and volume of weld bead deposited fixed, welds were made with a solid wire of carbon steel in an arc short enough to carry a transfer by way of short-circuit. The welding voltage was regulated to progressively vary transfer stability while maintaining the same average current. The quantification of transfer regularity was made through the Laprosolda criterion for short-circuiting metal transfer stability. Two conditions of low stability and one of high stability were used to assess the generation, morphology and composition of the fumes. The results showed that the Laprosolda Criterion proved accurate and it is an important tool which permits one to compare the effect of transfer regularity on the generation of fumes and gases, even under different shielding gases and parameters. The greater stability of metal transfer did not show, as expected, a lower rate of fume generation, even with less spatter. Because of this, different welding techniques were used to separate the effects of the welding parameters correlated to the short-circuiting metal transfer on the fume generation and checking governing principles. It was found that higher short-circuit currents, longer arc lengths and greater time with arc open contributed individually to an increase in the rate of fume generation, but if they acted together in the same direction, their contribution is significant. Also there is no evidence that a larger droplet diameter would decrease the rate of fume generation. The fumes generated mainly presented ultrafine particles (< 100 nm), and approximately round and with a composition of Fe, Mn and Si, C and O. However, the regularity of transfer did not show that it influenced morphology, size or composition of the fumes. The effect of the composition of the shielding gas was also verified, together with the current intensity and transfer regularity of the CO2 and CO emission. It was found that the richer the composition of CO2 of the shielding gas, the more CO and CO2 are generated by the arc. But, unlike fume emission, there is no effect of voltage, stability transfer and average current on the generation of these gases. It was also found that in spite of the large amount CO and CO2 emitted by the arc, especially when using pure CO2 protection, there was no significant concentration of them in the welder\'s breathing areas or proximity, not even in partially confined work cells.